Treating complete denture patients with xerostomia: knowledge, attitude and clinical management among dental practitioners of Chitwan - Khanal, Bibek; Thakur, Smriti Narayan; Sapkota, Srijana Mishra; Joshi, Kalit Raj; Pokhrel, Sushil (Journal of Chitwan Medical College, 2021)
Background: The absence or decreased amount of saliva in the oral cavity can cause severe discomfort to patients wearing complete denture like decreased denture stability and retention, ulcerations in the denture bearing tissues to name a few. This questionnaire-based study was conducted among dentists practicing in Chitwan, Nepal to find out their knowledge, attitude and management of complete denture patients with xerostomia. Methods: A cross-sectional study was performed among dentists in Chitwan. In total 103 dentists participated in this study. Descriptive statistical analyses were performed on the responses given by the dentists using SPSS Statistical Software package (version 21.0). Results: A total of 103 returned questionnaire were included in the study. Out of the responses analyzed, 99.02% (n=102) have heard about hyposalivation in patients who wear complete denture while 63.86% (n=62) of the respondents think that females suffer more often with xerostomia and 94.17% (n=97) respondents think unretentive denture and denture instability may be due to xerostomia. Likewise, 86.4% (n=89) of the respondents are aware of various tests to diagnose xerostomia and the same number of respondents have knowledge about drugs to treat hyposalivation in complete denture patients and role of salivary stimulants. Likewise 83.4% (n=86) of the respondents are aware of role of denture adhesives in managing such patients. Conclusions: From the responses obtained it can be concluded that the dentists of Chitwan have satisfactory knowledge about treating complete denture patients suffering from xerostomia.